Bioindicator and molecular-based water quality assessment of selected water bodies in Peninsular Malaysia / Davindran Rajandram - Davindran , Rajandram (2018)
Water bodies are essential to every living organism. A number of attributes such as temperature, dissolved mineral contents, can be used to assess whether or not the water body is contaminated with bacteria. In addition, water quality can be assessed using both physico-chemical parameters and bioindicators. Water quality assessment was performed using physico-chemical and biological aspects in two water bodies of varying location namely Fraser’s Hill and Pangkor Island. Between these two water bodies the physico-chemical properties that were found to be of significant difference was, amount of dissolved oxygen (DO), temperature (°C) and total suspended solid (TSS). There was no significant difference in the other tested parameters which were Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia Nitrogen (NH3-N) and pH. Test conducted using aquatic water beetles as bioindicators found that Fraser’s Hill had more diverse beetle families compared to Pangkor Island. On top of physico-chemical parameters and bioindicators, presence of bacteria was also studied using 16S rDNA to evaluate presence of bacteria in different water locations in these two water bodies. Bacterial DNA was detected in all the water samples collected from Pangkor Island whereas only one sample was detected in the Fraser’s Hill water sample. In conclusion, the water index (WQI) of the water bodies in Fraser’s Hill and Pangkor Island showed Class I and Class II readings respectively in line with the distribution of water beetle and presence of bacteria.